Factors impinging human capital of rural youth in Malaysia - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Abu Samah, Asnarulkhadi; Hamzah, Azimi; Idris, Khairuddin; Abu Samah, Bahaman (Medwell Journals, 2016)
The main aim of the present study is to identify the factors impinging the human capital of rural youth in Malaysia. The study is quantitative in nature whereby a developed questionnaire was used to collect the required data. Via a multi-stage cluster sampling, a total of 240 rural youth from four districts in Peninsular Malaysia had been selected as the respondents. Analysis performed confirmed that rural youth possessed a high level of human capital while specific analysis confirmed that there was a significant difference on human capital with the factor of occupation while significant relationship was detected between human capital and the factors of age and income. Several discussions have been highlighted and expectantly it can offer some ideas to the concerned parties in constructing strategies to further enhance the development of human capital among rural youth in Malaysia.